Morphological characterization and clustering analysis of three local jackfruit cultivars (Artocarpus heterophyllus) in Lamongan District, East Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ullah LR, Purnama PR, Wisanti. 2025. Morphological characterization and clustering analysis of three local jackfruit cultivars (Artocarpus heterophyllus) in Lamongan District, East Java, Indonesia. Biodiversitas 26: 1920-1928. Lamongan District is among jackfruit (Artocarpus heterophyllus) producers in East Java, Indonesia, where three local cultivars including `Nangka Bubur`, `Nangka Kandel`, and `Nangka Salak` have been identified. This study aimed to characterize and cluster the morphology of these 3 cultivars from Lamongan. Six trees per cultivar were assessed for 41 morphological characters (32 qualitative and 9 quantitative). Data were analyzed using Principal Component Analysis (PCA), k-means clustering, hierarchical clustering, correlation, and heatmap plots. Clustering methods successfully separated the tree cultivars. From the 41 characters, 4 uniform and least variance characters were excluded. Correlation analysis identified positively correlated characters such as spine density, fruit shape, spine diameter, falke texture, flake shape, and spine color. Based on variable importance plot, biplot PCA, and heatmap analysis, 11 diagnostic characters were identified: mesocarp thickness, spine length, pulp color at ripe stage, fruit shape, shape of spine, seed coat color, seed shape, flake texture, spine density, flake shape, and stalk attachment to fruit. The stated discoveries would provide helpful insight into the process of agricultural improvement, particularly concerning jackfruit.
Keywords: Artocarpus heterophyllus, clustering analysis, multivariate analysis, PCA, sustainable agriculture